Noise Reduction Algorithm Based on Template Wavelet Coefficients - Bezvesilniy, O.O.; Vynogradov, V.V.; Schuenemann, K. (Радиофизика и радиоастрономия, 2000)
In the paper, a new algorithm based on the application of template wavelet coefficients is proposed to solve the problems concerning noise reduction in the vicinity of edges in signals and images and suppressing parasitic oscillations, which arise when threshold wavelet algorithms are used. It is shown that this approach calls for choosing a specific wavelet. Examples of the application of the developed technique are given.